Sensitivity of impact behaviour of RC beams to contact stiffness - Pham, Thong; Hao, Y.; Hao, Hong (Elsevier, 2018)
© 2017 Elsevier Ltd It is commonly understood that the contact stiffness of the two colliding structures/objects is dependent primarily on the material properties. However, there have been experimental and numerical evidences that the contact stiffness is also strongly influenced by other factors. This study experimentally and numerically investigates the effects of contact stiffness on the impact behaviour of RC beams. Reinforced concrete beams were cast and tested under a drop-weight testing apparatus with different contact conditions simulating different contact stiffness. Extensive numerical simulations are carried out to confirm the findings from the experimental results and to perform parametric studies. The experimental and numerical results have shown that the contact stiffness is very sensitive to the actual setup in the experiment and contact condition, leading to a crucial effect on the peak value and duration of the impact force. The contact stiffness however has little effect on the impulse and thus the conversion of the impact energy to the beam and hence the midspan displacement. The magnitude of the inertia resistance is greatly influenced by the contact stiffness, resulting in a significant effect on the dynamic bending moment and shear force distribution along the beam. The contact behaviour needs to be carefully considered when analysing the impact behaviour of RC structures. In addition, advantages and disadvantages of the different contact algorithms in finite element packages, e.g. LS-Dyna, are discussed for a proper use in the simulation. An appropriate contact algorithm and a scale factor are greatly important to ensure the simulation properly reflects the actual contact problems, and they must be selected with extreme caution.